PENGARUH KEBIJAKAN HUTANG, KEBIJAKAN DIVIDEN, SIZE PERUSAHAAN DAN CASH HOLDINGS TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN-PERUSAHAAN YANG TERDAFTAR DI INDEKS KOMPAS 100) - admin, SELVI ROSAMIN B11112001 (Jurnal Manajemen Update, 2016)
One of the company's main goals is to maximize the value of the company. The value of the company is an investorâ€™s perception of the level of success of companies that are often associated with stock prices. This research aims to analyze the effect of the debt policy (DER), the dividend policy (DPR), firm size and cash holdings to the value of the company on the companies listed in the Index Kompas 100 with period 2010-2014. The research sample used a purposive sampling method, which used 22 companies as the sample with a total of 110 observations. The data used was secondary data, and the technique of analysis used multiple linear regression analysis. Results of regression analysis in this research showed: the debt policy (DER) and the firm size partially have a negative significant effect on the firm value, while dividend policy and cash holdings have no significant effect on the firm value. The coefficient of determination showed a value of 0.353 means that the dependent variable can be explained by four independent variables with the value of 35.3%, wwhile the rest of 64.7% is explained by other variables outside the research model. Keywords : Debt to Equity Ratio, Dividend Payout Ratio, Firm size, Cash Holdings, FirmÂ  Value